2017
DOI: 10.1038/s41598-017-09335-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrative epigenomics, transcriptomics and proteomics of patient chondrocytes reveal genes and pathways involved in osteoarthritis

Abstract: Osteoarthritis (OA) is a common disease characterized by cartilage degeneration and joint remodeling. The underlying molecular changes underpinning disease progression are incompletely understood. We investigated genes and pathways that mark OA progression in isolated primary chondrocytes taken from paired intact versus degraded articular cartilage samples across 38 patients undergoing joint replacement surgery (discovery cohort: 12 knee OA, replication cohorts: 17 knee OA, 9 hip OA patients). We combined geno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 59 publications
(59 reference statements)
8
97
0
1
Order By: Relevance
“…151 Studies integrating transcriptomics, epigenomics, and proteomics data from human OA chondrocytes have uncovered pathways differentially modulated in OA disease. 152 One study has shown an overall increase in methylation accompanied by reduced expression of transcription factors in OA compared to healthy cartilage. 153 Changes in DNA methylation associated with OA progression are also observed in subchondral bone, with an enrichment of genes involved in morphogenesis and development of the skeletal system in OA samples, 154 highlighting the contributions of developmental pathways in the disease context.…”
Section: Figure 4 Modulation Of Chondrocyte Hypertrophy By Canonicalmentioning
confidence: 99%
“…151 Studies integrating transcriptomics, epigenomics, and proteomics data from human OA chondrocytes have uncovered pathways differentially modulated in OA disease. 152 One study has shown an overall increase in methylation accompanied by reduced expression of transcription factors in OA compared to healthy cartilage. 153 Changes in DNA methylation associated with OA progression are also observed in subchondral bone, with an enrichment of genes involved in morphogenesis and development of the skeletal system in OA samples, 154 highlighting the contributions of developmental pathways in the disease context.…”
Section: Figure 4 Modulation Of Chondrocyte Hypertrophy By Canonicalmentioning
confidence: 99%
“…Full details for confirmation of joint replacement for osteoarthritis and cartilage tissue scoring are listed in Supplementary Methods. We followed previously established protocols to isolate chondrocytes 37,38 , and synoviocytes 39 DNA, RNA and protein extraction DNA, RNA, and protein extraction was carried out using Qiagen AllPrep DNA/RNA/Protein Mini Kit following manufacturer's instructions, with small variations for cohort 3 as previously described 38 . Samples were frozen at -80C (cohorts 1, 2, 4) or -70C (cohort 3) prior to assays.…”
Section: Study Participantsmentioning
confidence: 99%
“…Proteomics analysis was performed on cartilage samples from 103 patients ( Supplementary Table 9). For cohort 1, all steps of protein digestion, 6-plex TMT labelling, peptide fractionation and LC-MS analysis on the Dionex Ultimate 3000 UHPLC system coupled with the high-resolution LTQ Orbitrap Velos mass spectrometer (Thermo Scientific), were previously described 37 . The sample preparation protocol formed the basis of processing for cohorts 2-4 using 10-plex TMT labelling and an Orbitrap Fusion Tribrid Mass Spectrometer (Thermo Scientific) with otherwise only minor alterations (e.g.…”
Section: Proteomicsmentioning
confidence: 99%
“…Further comparison with published ageing or osteoarthritis-regulated cartilage proteomic studies [15][16][17][18][19][20][21][22] revealed a list of 34 rhythmic proteins being dysregulated in disease condition and/or in aging (Table 1).…”
Section: Figure 2 Protein Interaction Network Of Rhythmic Proteins Smentioning
confidence: 99%